Centimeter‐Scale PdS2 Ultrathin Films with High Mobility and Broadband Photoresponse. Issue 17 (1st February 2023) - He, Kun; Xu, Weiting; Tang, Jingmei; Lu, Yuan; Yi, Chen; Li, Bailing; Zhu, Hongzhou; Zhang, Hongmei; Lin, Xiaohui; Feng, Ya; Zhu, Manli; Shen, Jingru; et al.
Abstract: 2D materials with mixed crystal phase will lead to the nonuniformity of performance and go against the practical application. Therefore, it is of great significance to develop a valid method to synthesize 2D materials with typical stoichiometry. Here, 2D palladium sulfides with centimeter scale and uniform stoichiometric ratio are synthesized via controlling the sulfurization temperature of palladium thin films. The relationship between sulfurization temperature and products is investigated in depth. Besides, the high‐quality 2D PdS2 films are synthesized via sulfurization at the temperature of 450–550 °C, which would be compatible with back‐end‐of‐line processes in semiconductor industry with considering of process temperature. The PdS2 films show an n‐type semiconducting behavior with high mobility of 10.4 cm 2 V −1 s −1 . The PdS2 photodetector presents a broadband photoresponse from 450 to 1550 nm. These findings provide a reliable way to synthesizing high‐quality and large‐area 2D materials with uniform crystal phase. The result suggests that 2D PdS2 has significant potential in future nanoelectronics and optoelectronic applications. Abstract : This study reports the synthesis of palladium sulfides with centimeter scale and uniform stoichiometric ratio via controlling the sulfurization temperature of palladium thin films. The PdS2 films show an n‐type semiconducting behavior with high mobility of 10.4 cm 2 V −1 s −1 and present a broadband photoresponse from 450 to 1550 nm.